Pengaruh Pendekatan Pembelajaran Discovery Learning pada Hasil Belajar Siswa - Ramadhani, Atha Haryo (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
In order to achieve a learning goal, educators must know how to organize classes well and how to grow good learning outcomes. One way that can be taken is the use of a learning approach that is tailored to the characteristics of students, one of the approaches used is the discovery learning approach, this learning approach provides opportunities for students to be active, increase self-confidence, and be able to think for themselves and direct students to study harder. This learning also motivates students to learn independently and be able to find their own answers. The results of research conducted by observers, this learning approach has succeeded in improving student learning outcomes in learning